2017
DOI: 10.22159/ajpcr.2017.v10i12.19348
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking, Molecular Dynamics, and in Silico Toxicity Prediction Studies of Coumarin, N-Oxalylglycine, Organoselenium, Organosulfur, and Pyridine Derivatives as Histone Lysine Demethylase Inhibitors

Abstract: Objective: Prostate cancer is the second most common cancer in men. One of the efforts in the treatment of prostate cancer is by inhibiting histone lysine demethylase. Derivative compounds of coumarine, N-oxalylglycine, organoselenium, organosulfur, and pyridine have been reported to be active against two types of histone lysine demethylase (KDM) enzymes, KDM4E and KDM5B. This study aims to study the interactions of these derivatives with KDM. Methods:In this study, we performed computational studies, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The simulation preparation stage includes minimization, heating to 310 K, temperature equilibration, pressure equilibration, and a 500 ns production run with a 2 fs timestep 15, 16 .…”
Section: Glimepiride-metformin Interaction Dynamicsmentioning
confidence: 99%
“…The simulation preparation stage includes minimization, heating to 310 K, temperature equilibration, pressure equilibration, and a 500 ns production run with a 2 fs timestep 15, 16 .…”
Section: Glimepiride-metformin Interaction Dynamicsmentioning
confidence: 99%
“…Twelve flavonol derivative compounds were docked onto the macromolecular target (Bcl-2, PDB ID: 3SPF). The results showed that only six ligands (3,5,7,8,9, and 11) had a low binding free energy with inhibition constant lower than 1 µM (Table 2), showing a promising sign that these ligands have good affinities toward their target. Ligand eight is the best ligand which binds the active site of Bcl-2 receptor with a binding free energy of -37.739 kJ/mol and the inhibition constant of 0.246 µM.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…One of the stages in the process of discovering new drug compounds is the study of interactions between drug candidate compounds and receptors. This can be done in in-silico through molecular docking and molecular dynamic simulations (Muttaqin, et al, 2017). Docking is a method for predicting the best orientation of a molecule when bound to one another to form stable complexes.…”
mentioning
confidence: 99%
“…In view of the biotechnological importance of such type of material necessitates the generalization of such type of expanded genetic code which needs more physical parameters. Molecular dynamics simulations is one of the most emerging methodologies in structural and molecular biology, and widely used to explore the structure, conformational aspects and binding affinities of biomolecules [14][15][16][17][18]. As an attempts to characterize the conformation of hydrophobic, unnatural base-pair, the conformational parameters of the complexes leading to the insertion of DNAM opposite to D5sics in DNA-duplex we modelled 14-mer DNA strands of sequences d(GTCDNAM GCGCCGTGGC).…”
Section: Fig 1: Dsics-mmo2 and D5sics-dnam Base-pairmentioning
confidence: 99%